Academic motivation through the experience of older women university students in Mexico during the 2025 school period - De León, César (2025)
In the educational context, academic motivation is an individual characteristic associated with various indicators of academic achievement. However, few studies have explored this variable among students over 60 years of age, creating a gap in the understanding of academic motivation in later life. The purpose of this study was to describe academic motivation from the experiences of older adult women enrolled in higher education. A qualitative and phenomenological study was conducted with the collaboration of six older adult women enrolled in two higher education academic programs, aged 60 to 65 years, using an interview guide to collect information. The content analysis identified five categories that make up academic motivation in older female university students: family support, self-fulfillment, academic support, job expectations, and amotivation. Among the findings, it is noteworthy that academic motivations focus on the support received from children and partners, the achievement of personal and professional goals, and the support of teachers. The findings are expected to inform the development of inclusive educational policies that promote the participation and persistence of older adults in university settings.